Effect of Fluorine on the Structure and Properties of Some Silicate Glasses - Abd-El Mongy, A.; Madkour, H.; Taha, M.; Shaikh, H.El. (Asian Journal of Chemistry, 2012)
Of alkali silicate glasses containing fluorine, the d.c. conductivity and density values decreased as fluorine substitutes oxygen. The conductivity was attributed to ionic transport of alkali ion as well as electron hopping transport, the increase of non-bridging oxygen as fluorine content increase explains the decrease of density. However infrared absorption increased as fluorine content was increased. At higher fluorine concentrations, new bands appeared in infrared spectrum.